Potential of ground sink heat pump for small scale air conditioning system - Wan Nurfarzana Wan Mazlan (Penerbit Universiti Malaysia Perlis, 2011)
In the pursuit of sustainable environment, systems with high efficiency and produce less pollution are brought into perspective. Geothermal would provide a solution for energy efficiency and an option of renewable energy. Ground Sink Heat Pump (GSHP) system is an air conditioning system that uses the Earths ability to store heat in the ground and water thermal masses. In this project, it showed the comparison design installation between a GSHP system and an Air Source Heat Pump (ASHP) system which acts GSHP as an effective air-conditioner and eco-friendly, using natural characteristics of the Earths surface. The systems connected to a test room in School of Environmental Engineering UniMAP were designed and constructed for space cooling. The performance of GSHP and the ASHP system were experimentally determined. The power consumption for GSHP in the range in 0.21 to 0.46 kWh and for ASHP in the range 0.33 to 0,38 kWh has been consumed per day. Besides that, the sizing and costing of the proposed system had been determined. The test room and ground loop had been designed in size of the room 2 meter length, 2 meter high and 1 meter width. The GSHP system was operated and tested in during the cooling season in the School of Environmental Engineering UniMAP, which presents a great potential for commercialization of GSHP. Based on the results, it was proven that the potential of GSHP for small scale air conditioning system can be more efficient when some recommendation were added such as select the correct equipment, check site access for equipment to install a GSHP and others.